1949
DOI: 10.5254/1.3542975
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Electrostatic Charges Produced during Mastication of Rubber and of GR-S

Abstract: A new electrostatic field strength meter has been described which measures and records, not only the magnitude of electrostatic fields, but also their polarity. This device has been used in a study of the mastication of rubber, and has furnished data which indicate that rubber becomes less negative, and may actually become positive, as mastication proceeds ; this indicates in turn an oxidation of the molecules as well as an electronic rearrangement and orientation of the rubber molecular chains. Data on GR-S p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1949
1949
1953
1953

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is well knowm that the breakdown of rubber by mastication is an oxidation process; how-ever, the mechanism of the plasticizing action of the chemical plasticizers or peptizers, as they are often called, is not so well knowm. In a previous paper (3), it was shown that as rubber w-as masticated the electrical potential went from a highly negative value to a positive value. This loss of electrons, or increase in positive charge, indicated that the breakdown of rubber by mastication was an oxidation reaction.…”
Section: Chemical Plasticizing Actionmentioning
confidence: 93%
“…It is well knowm that the breakdown of rubber by mastication is an oxidation process; how-ever, the mechanism of the plasticizing action of the chemical plasticizers or peptizers, as they are often called, is not so well knowm. In a previous paper (3), it was shown that as rubber w-as masticated the electrical potential went from a highly negative value to a positive value. This loss of electrons, or increase in positive charge, indicated that the breakdown of rubber by mastication was an oxidation reaction.…”
Section: Chemical Plasticizing Actionmentioning
confidence: 93%
“…Havenhill, Carlson, Emery, and Rankin (122,123) described a new electrostatic probe and associated equipment for detecting and recording both the polarity and magnitude of electric charges formed when rubber batches are mixed in a Banbury mixer. These contact potentials produce strong electrostatic fields from which one may obtain fundamental information on the mastication, incorporation, and dispersion of softeners and pigments.…”
Section: Aging and Deteriorationmentioning
confidence: 99%
“…A new "electrostatic probe" and associated equipment have been described for measuring and recording the changes in electrical potential of the rubber batch in the Banbury mixer (66). By this means the breakdown of the rubber and the state of incorporation of the pigment, oils, and other ingredients can be followed without raising the ram.…”
Section: Physical Propertiesmentioning
confidence: 99%